Pengaruh Kualitas Auditor Dan Komite Audit Terhadap Audit Delay Pada Perusahaan Food And Beverage Yang Terdaftar Di BEI - Anjar Prianti; Dirvi Surya Abbas (LPPM Universitas Putera Batam, 2022)
The purpose of this research is to determine the effect of audit quality, and audit committee the audit delay. Independent variables used in this research is audit quality and committee audit. While the dependent variable for this research is the audit delay. The selectiom of the sample in this research is using the purposive sampling method. The selected sample in this research are 10 food and beverage companies oh the IDX the period of 2016 – 2019. The results showed that audit quality has a significant positive effect on audit delay, audit committee has a significant positive effect on audit delay.